Efecto de Escherichia coli y Salmonella spp en el crecimiento y mortalidad de crías de alpacas (Vicugna pacos) - Carhuapoma D., Víctor (2019)
The aim of this study was to evaluate the effect of E. coli and Salmonella spp on the growth and mortality of baby alpacas (Vicugna pacos). It was selected 104 Huacaya alpacas with diarrheal processes and with an average age of 10.0 ± 2 days, body weight of 9.6 ± 0.5 kg and height at the withers of 85.0 ± 0.5 cm. Samples of rectal swabs were cultured in selective culture media of MacConkey, EMB, SS, XHD and BIH agar, and biochemical tests were performed. Based on the positive results of E. coli and Salmonella spp. A total of 80 animals were selected and assigned into four groups: G1, E. coli (n=23); G2, Salmonella spp (n=17); G3, E. coli – Salmonella spp (n=12); G4, control (n=28), positive for one or both germs and treated with tetracycline. The animals were weighed and measured (height at the withers) at weeks 4 and 8 of the study and mortality was recorded. The weight and corporal height were more affected in G1, G2 and G3 that the G4 (p<0.01). Likewise, the rate of mortality was major in G1, G2 and G3 and in G4 in both sexes. Salmonella spp and E. coli affected the growth and caused mortality in baby alpacas with diarrhoea.